Dengue diagnosis in an endemic area of Peru: Clinical characteristics and positive frequencies by RT-PCR and serology for NS1, IgM, and IgG - Palomares-Reyes, Carlos (2019)
This work was supported by Cienciativa of CONCYTEC Peru, under contract number 164-2016-FONDECYT, and the Programa Nacional de Innovación para la Competitividad y Productividad (Innóvate Perú), under contract number 116-PNICP-PIAP-2015.